Transfer of Oral Literature: The Folk Story of Galunggung Tasikmalaya into Drama Text as a Culture Conservation Effort - Budi Riswandi; Ai Siti Nurjamilah; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2021)
Oral literary works usually produce works related to culture because they develop by word of mouth in the community. Oral literature is one of the cultural heritages originating from the community. One of the oral literature that develops in the community is folk prose or folklore. Folklore is said to be a cultural heritage because it usually expresses an event or occurrence that comes from a certain region or area and can be a toponymous story of an area. One of the folk prose or folklore that developed in the community is the folklore of Mount Galunggung originating from the City of Tasikmalaya, West Java. This study tries to transfer folklore into the form of drama texts as an effort to preserve culture by using descriptive research and literature. The folklore was converted into a one-act drama text that tells about Raden Anom Aria's deliberation with the ulama, traditional elders, and the people of Galunggung to establish the Galunggung Kingdom. The content of the drama text emphasizes more on the deliberation process. The changes made are the shrinking of the plot, setting, and characters into a one-act drama text consisting of three scenes. The characters presented include: a) Raden Anom Aria; b) White Kuncung Batara; c) Ulama (Shaykh), and the people of Galunggung to establish the Kingdom of Galunggung. The content of the drama text emphasizes more on the deliberation process. The changes made are the shrinking of the plot, setting, and characters into a one-act drama text consisting of three scenes. The characters presented include: a) Raden Anom Aria; b) White Kuncung Batara; c) Ulama (Shaykh), and the people of Galunggung to establish the Kingdom of Galunggung. The content of the drama text emphasizes more on the deliberation process. The changes made are the shrinking of the plot, setting, and characters into a one-act drama text consisting of three scenes. The characters presented include: a) Raden Anom Aria; b) White Kuncung Batara; c) Ulama (Shaykh), d) Traditional Elders, and e) People. Based on the results of this vehicle transfer research, it can be concluded that folklore can be used as a source of ideas or references for making drama scripts, whether they are staged or not. In addition, by carrying out the process of transferring folklore into drama, it will at least attract the attention and interest of the current generation.